Pulmonary lesions in guinea pigs experimentally infected with Actinobacillus pleuropneumoniae (A.p.) serovar 1. - Perfumo, Carlos Juan (1999)
Pathological studies were carried out on the lungs of guinea pigs intratracheally inoculated with 4.6 × 106-8 colony forming units (CFU)/head of Actinobacillus pleuropneumoniae serovar 1. All animals in the highest dose group died within 24 hr post inoculation (hpi) and showed pulmonary lesions being hemorrhagic in nature while all animals in the lowest dose group were killed as scheduled at 11 days post inoculation (dpi) and showed only hyperplasia of peribronchial lymphoid tissues. In the middle dose group, two died within 24 hpi, two died at 9 dpi, and the remaining one was killed at 11 dpi. Two guinea pigs which died at 9 dpi showed fibrinonecrotic pleuropneumonia which is the most characteristic acute pulmonary lesion in swine, and has not yet been reproduced in laboratory animals up to the present time. This suggests that guinea pigs may be a useful laboratory animal for studying the pathogenesis of Actinobacillus pleuropneumoniae infection in swine.